Portrayals of Economic Exchange in the Book of Kings - Nam, Roger S. (Leiden : BRILL, 2012)
Drawing on the Polanyian categories of reciprocity, redistribution and market trade, this book examines the exchange narratives within 1 and 2 Kings in an effort to clarify the nature of the economic structures behind the biblical text.
5.3. References to Silver5.4. Did Israel Know Price Setting Markets?; 5.5. Summary and Conclusions; Chapter Six A Social Analysis of Exchange in the Book of Kings; 6.1. Ancient Israel as a Mixed Economy; 6.2. Ancient Israel as an Informal Economy; 6.3. The Economic System of Israel and Judah; 6.3.a. The Local Economy; 6.3.b. The International Economy; Chapter Seven Summary and Conclusions; 7.1. Overall Summary and Conclusions; 7.2. Directions for Future Research: Post-exilic Portrayals of Economic Exchange; Select Bibliography; Index of Ancient Sources; Index of Modern Authors; Subject Index.
Description based on print version record.
Keywords: Bible. -- O.T. -- Kings -- Criticism, interpretation, etc; Economics in the bible; Religion; Bible. -- Criticism, interpretation, etc; Economics in the Bible; RELIGION / Biblical Studies / Old Testament; Electronic books